THE INFLUENCE OF RETARDANTS AND SUPPLEMENTARY FERTILIZATION ON THE GROWTH AND YIELD OF INDUSTRIAL POTATO - Devita Aprilia; Jajang Sauman Hamdani; Rahmat Budiarto (UIN Sunan Gunung Djati Bandung, 2026)
The low productivity of potatoes in Indonesia is attributed to the use of low-quality seed tubers, limited agricultural land, and suboptimal cultivation practices. Therefore, the application of gibberellin-inhibiting growth regulators may serve as a strategy to improve potato productivity, including paclobutrazol and prohexadione-Ca. This study aimed to determine the effects of paclobutrazol, prohexadione-Ca, and supplementary fertilization on the growth and yield of G2 potato seed tubers of the Medians cultivar. The experiment was conducted from October 2025 to January 2026 at PT. Horti Agro Makro, Cisurupan District, Garut, West Java, located at an altitude of approximately ± 800 m asl. The experimental design used was a Split Plot Design. The first factor, assigned as the main plot, consisted of growth retardants: paclobutrazol at 100 ppm and prohexadione-Ca at 100 ppm. The second factor, assigned as the subplot, consisted of supplementary fertilizer treatments: Urea, Urea + ZA, Urea + MgSO4, and Urea + Humate NPK. The results showed a significant interaction between paclobutrazol and Urea + MgSO4 on tuber water content (76.14%). Paclobutrazol application had a significant independent effect in reducing plant height, and leaf area index, while increasing tuber weight (752.39 g). The application of Urea + MgSO4 as a supplementary fertilizer significantly reduced the plant height, while increasing the tuber weight, and specific gravity.